Assessment of the Impact of Housing Affordability among the Low Income Residents in Ibadan North Local Government Area, Oyo State Nigeria - Taiwo Oluwafunmilayo Favour (Archives of Current Research International, 2025)
The study aims to assess the impact of housing affordability among the low income groups so as to provide a sustainable housing delivery in Ibadan North Local Government Area in Ibadan, Oyo state Nigeria. Affordability theory provided the theoretical anchor, while cross survey research design was adopted for the study. Both primary and secondary data were sourced. Using a purposive multi stage sampling technique, a structured questionnaire was administered to 186 respondents. Field observation with aid of checklist was used to complement the data. Variables that were addressed include, the determinants of disposable income of housing affordability, the influence of housing affordability on housing the low income earners, the effects of socio economic status on the resident’s housing satisfaction. Both quantitative and qualitative analysis were used to analyse the data p < 0.05. Field observation was utilized in carrying out this research. The findings also revealed the predominance (62.4%) of housing unaffordability and the inadequacy of the basic housing infrastructure in the study area. Affordability was difficult among the low income earners. The study therefore recommends the social housing provision by the government.